The Analysis of Mathematics Question Items Quality at SMPN 01 Pakusari In the Online Learning Period - Fadhilatus Sholihah; Tri Susilaningtyas; Fury Styo Siskawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
The purpose of this study was to describe the quality of math problems with integer material for class VII A SMP 01 Pakusari during the online learning period. The quality of the analyzed items was reviewed in terms of validity, reliability, differentiation and difficulty level. This research is a descriptive study with a qualitative approach. The subjects in this study were class VII A with 32 students. Based on the results of the study, it can be concluded that the quality of the mathematical questions with the integer material in terms of the validity of the questions that were declared valid were 13 questions (62%) and there were 8 invalid questions (38%). In terms of reliability, there were 21 questions (100%) and 0% unreliable questions with a total r11 of 0.71. In terms of distinguishing power, there are 3 questions (14%) with good distinguishing power, 1 question (5%), 2 questions (10%), 2 questions (10%) have bad distinguishing power there are 15 questions (71%). In terms of difficulty level, there are 7 questions in the difficult category (33%). There were 12 questions in the medium category (57%) and there were 2 questions in the easy category (10%). Keywords: quality of question items, online learning period